Care coordination for children with special health care needs: a cohort study. Issue 1 (January 2017) - Zanello, Elisa; Calugi, Simona; Sanders, Lee; Lenzi, Jacopo; Faldella, Giacomo; Rucci, Paola; Fantini, Maria
Abstract Background Care coordination is widely recognized as a key element of care for patients with chronic and complex medical conditions and their families. In care for children with special health care needs the Family Pediatrician (FP) plays a central role as care coordinator. This study aims to evaluate the FPs' activities of care coordination for children with special health care needs in the pediatric primary care setting, using an on-line measurement tool. Methods Within the prospective cohort study SpeNK (Special Needs Kids), newborns and children with special health care needs were recruited at discharge from three hospital facilities in Bologna province, from October 1st 2012 to September 30th 2014. Their FPs were invited to complete a questionnaire (SpeNK-FP) at each encounter for the patient during a 9-month period after hospital discharge. SpeNK-FP was developed by adapting the Care Coordination Measurement Tool (CCMT©) developed by Antonelli et al., to the Italian organizational context. The outcome of interest, derived from the questionnaire, is inappropriate use of services. Results Forty FPs completed assessments for 49 children at each of 382 clinical encounters. The majority of children (71.4%) had special health care needs, without complicating social issues. FPs reported "no need for care coordination" in 50.8% of the encounters and 41.1% of records about patient needs requiring care coordination. The most common activity implemented to meet children's needs was telephone contact with a medical provider. According to FPs, 80% of encounters prevented inappropriate services use. In multivariate regression, pediatric-specialist contact (telephone or in person) was associated with reduced odds of physician report of preventable hospitalization (OR = 0.06, 95% CI 0.01–0.42, p  = 0.005). Conclusions The study shows the potential for FPs in Italy to serve as care coordinators and facilitate the implementation of integrated care pathways for children with special health care needs.